(untitled) (Fiep Bulletin - online, 2014)
from the antiquity the physical activity has been prescribed in the treatment of several illnesses and as form of preventing pathologies in the human body. In modern world academic studies demonstrating the importance of the physical activity in the man’s health conditions. We know that lifestyle is one of the factors that causes diseases in the present society, owed mainly to the sedentary life and unhealty habits of feeding. Physical activity becomes indispensable to avoid several illnesses that cause disability and precocious death. When the people increase their levels of physical conditioning, they move forward towards a better quality of life with full accomplishment social, psychic, spiritual, labor, getting to surpass the stress and the depression. Several ways, the life activates and physical fitness represents economy, reducing futures medical expenses, reducing the need of lingering cares and eliminating deep responsibilities for the family and the society. The physical activity to regulate it serves as a strategy of positive health, as amusement amid the lifestyle disturbed that the people take in the technological world of the present time, where the home, the family and the humanistic values are in an inferiority plan. No pharmacological treatment of the insomnia it is important for senior people, because has as objective the patient’s education regarding the cares of the therapy and his involvement with the same. The people with disturbance of the cycle sleep/vigil need to know the normal patterns of the sleep in the old age, in order to develop healthy habits that they promote the sleep, calls of hygiene of the sleep, including the adhesion to a schedule to regulate of sleep, avoiding stimulants and alcohol, limitation of the naps during the day, physical activity and regular recreation.